2016
DOI: 10.5152/kd.2016.04
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude of Family Physicians About Human Papilloma Virus and Herpes Zoster Vaccines

Abstract: Objective: In this study, it is aimed to examine knowledge and attitudes about HPV and herpes zoster vaccines among family physicians. Methods: The study was conducted at 5th Annual International Family Practice Congress (19-23 Decembe, 2014, Antalya, Turkey) using face-to-face survey forms handed out to 263 family physicians. Statistical data has been analyzed using STATA 9.0 program. Results: Majority of the participants (89.3%) had knowledge about HPV vaccine and 156 (59.5%) of them had been recommending th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…A prospective study carried out at five centers in Turkey ( N = 155) reported that 12.7% of individuals had knowledge of HZ vaccination [ 97 ], while another survey of 100 participants aged 19–63 years in Anatalya noted that only 1% had knowledge of HZ vaccination [ 96 ]. However, a survey of 263 Turkish family physicians in 2014 revealed that 59.7% had knowledge of HZ vaccination and 65.7% would recommend the vaccine [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…A prospective study carried out at five centers in Turkey ( N = 155) reported that 12.7% of individuals had knowledge of HZ vaccination [ 97 ], while another survey of 100 participants aged 19–63 years in Anatalya noted that only 1% had knowledge of HZ vaccination [ 96 ]. However, a survey of 263 Turkish family physicians in 2014 revealed that 59.7% had knowledge of HZ vaccination and 65.7% would recommend the vaccine [ 103 ].…”
Section: Resultsmentioning
confidence: 99%